Impact of the COVID-19 pandemic on the volume and diagnoses of patients admitted to the paediatric emergency department: a retrospective analysis from a third-level hospital in Northeastern Mexico - Paulina Blanco-Murillo; Ricardo J Estrada-Mendizabal; Katheryne Paola Madrazo-Aguirre; Manuel Guillermo Ruelas-Martinez; Lucia Escobedo-Berumen; Rommy Elizabeth Pineda-Magaña; Maria Guadalupe Garcia-Lima; Oscar Tamez-Rivera (BMJ Public Health)
Background During the COVID-19 pandemic, there were noticeable changes in the number of admissions to paediatric emergency departments (EDs) worldwide, as well as in the patient’s diagnoses. There is scarce evidence about the impact of the pandemic on paediatric EDs in Latin America and Mexico. This study aimed to analyse the changes in volume and discharge diagnoses of patients admitted to a third-level paediatric ED in northeastern Mexico before and during the COVID-19 pandemic.Methods A retrospective observational study was carried out to compare the number of admissions and discharge diagnoses between two 3-month periods: December 2020–February 2021 (prepandemic) and December 2019–February 2020 (pandemic). Other variables, such as age, sex and comorbidities, were analysed. χ2 and Mann-Whitney U tests were used depending on the examined variable.Results There was a 44.1% decrease in the total volume of patients admitted to the paediatric ED during the analysed pandemic period. The percentage of infectious diseases decreased from 45.7% to 19.3% (p<0.001), and respiratory diseases from 4.3% to 1.9% (p<0.001), including asthma exacerbations (3.1%–1.5%, p=0.012). There was an increase in the percentage of patients admitted due to accidents (6.6%–14.7%, p<0.001).Conclusions A significant decrease in the total volume of patients, especially those who were admitted due to infectious and respiratory diseases, was documented. Gaining deeper knowledge of the impact of global health emergencies on the use of healthcare services is crucial for an adequate planning of resource allocation in case of future pandemics.